2018
DOI: 10.3390/ijerph15081787
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Coping with Job Loss. Empirical Study to Contribute to the Development of Unemployed People

Abstract: Having a job is an essential part of people’s development. Unemployment, on the contrary, is one of the most frustrating experiences of life with greater psychological consequences for people’s lives. In this sense, psychology has contributed to an increase in knowledge about the personal and social experience of unemployment. This article discusses indicators of anxiety and depression in unemployed people, modulating socio-demographic variables, and coping strategies involved in the higher and lower levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
4
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
0
13
4
6
Order By: Relevance
“…(PHQ-9) as compared to the result of our study (30.9%). Also the results of studies conducted in Spain (51.5%) [23], Korea (39.5%) [24] and Bangladesh (49.3%) [25] were higher than the findings of our study.…”
Section: Discussioncontrasting
confidence: 96%
“…(PHQ-9) as compared to the result of our study (30.9%). Also the results of studies conducted in Spain (51.5%) [23], Korea (39.5%) [24] and Bangladesh (49.3%) [25] were higher than the findings of our study.…”
Section: Discussioncontrasting
confidence: 96%
“…(PHQ-9) as compared to the result of our study (30.9%). Also the results of studies conducted in Spain (51.5%) [23], Korea (39.5%) [24] and Bangladesh (49.3%) [25] were higher than the finding of our study.…”
Section: Discussioncontrasting
confidence: 95%
“…Another study conducted in Germany also reported the higher prevalence of depression (34.4%) among longterm unemployed people measured by using Patient Health Questionnaire-9 (PHQ-9) as compared to the result of our study (30.9%). Also the results of studies conducted in Spain (51.5%) [23], Korea (39.5%) [24] and Bangladesh (49.3%) [25] were higher than the finding of our study.…”
Section: Discussioncontrasting
confidence: 95%